Exiting the fragility trap: Rethinking our approach to the world's most fragile states - David Carment; Yiagadeesen Samy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Those fragile states whose stagnation is so tenacious despite generous aid programs, and substantial and costly interventions, are stuck in a 'fragility trap.' Caught in a low-level equilibrium, trapped states appear to be in a perpetual political and economic limbo that can last for years and in several cases, decades. Our goal is to determine those features that trapped states have in common, and compare changes in those features over time with states that have successfully exited. The paper unfolds in four parts. In the first part we examine key concepts underpinning fragility traps in addition to conducting a review of current theorizing. In the second part we present the results of our large sample analysis. In the third part we compare the results of our comparative case studies with findings from the large sample analysis. In the fourth and final section we conclude with a discussion on how our findings inform policy.
Keywords: 330; fragile states; Mali; Bangladesh; Yemen; Pakistan; Mozambique; Laos